The Phenotypic Performances of Gerbera Local Bali X Rubby Red Hybrids - Yuniarto, Kurnia; Kurniati, Ridho; Suryawati, Suryawati; Meilasari, Rika (AGRIVITA, Journal of Agricultural Science, 2018)
Gerbera is one of important cut flowers in floriculture industries. It can substitute of chrysanthemum. The novelty of cultivar and superiority of characteristic of gerbera are necessary in the floriculture markets. New cultivars can be created through hybridization between cultivars. This study aimed to find out the phenotypic performances of gerbera hybrids of Local Bali x Rubby Red. The research was conducted in Indonesian Ornamental Crops Research Institute, West Java, Indonesia from January 2014 to September 2015. Eight progenies of F1 hybrids and their parents (Local Bali and Rubby Red) were used as materials. In the hybridization process Local Bali and Rubby Red were used as female and male parents respectively. Genetic variabilities of Gerbera were achieved through this hybridization. Gerbera progeny no. 20.009 had the longest inflorescence diameter, the biggest outer sepal and the highest number of sepals compared to the others. The flower vase life of this progeny was not significantly difference to the male parent. Qualitative characters observation showed that the hybrids were classified into two groups based on flower type, four groups of outer ray florets and two-disc groups of petal color.